Turnout and the modeling of economic conditions : evidence from Portuguese elections - Martins, Rodrigo Caldeira de Almeida (2012)
This paper analyzes the impact of economic conditions on voter turnout at Portuguese legislative and municipal elections. We use four extensive datasets to estimate an economic turnout model in which local economic variables are included in quadratic form, so that non-linear effects can be taken into account. The first two datasets cover all mainland municipalities (currently 278), from 1979 to 2005. The other two are cross-sections of all 4037 mainland freguesias, used to analyze the determinants of turnout at the 2001 municipal elections and at the 2002 legislative elections. Empirical results indicate that the performance of the national economy is important only in legislative elections and that, in accordance with our expectations, the regional and local unemployment rates tend to have a non-linear relationship with turnout.